A 108.83-m ice-core record of atmospheric dust deposition at Mt. Qomolangma (Everest), Central Himalaya - Xu, Jianzhong; Hou, Shugui; Qin, Dahe; Kaspari, Susan; Mayewski, Paul Andrew; Petit, Jean Robert; Delmonte, Barbara; Kang, Shichang; Ren, Jiawen; Chappellaz, Jerome; Hong, Sungmin (Quaternary Research, 2010)
International audience The central Himalaya can be regarded as an ideal site for developing a long-term ice core dust record to reflect the environmental signals from regional to semi-hemispheric scales. Here we present a dust record from segments of a 108.83-m ice core recovered from the East Rongbuk (ER) Glacier (27°59′N, 86°55′E; 6518 m a.s.l.) on the northeast slope of Mt. Qomolangma (Everest) in the central Himalaya, covering the period AD 600-1960. Due to rapidly layer thinning and coarse sampling, we primarily discuss the changes in the dust record since AD 1500 in this paper. Results show a significant positive relationship between the dust concentration and reconstructed air temperatures during this period, suggesting a likely cold-humid and warm-dry climatic pattern in the dust source regions, namely Central Asia. This is associated with the variability in the strength of the westerlies and its corresponding precipitation.